Avaliação sensorial de bebida à base de mangaba - Lima, Bárbara Paiva de; Perfeito, Danielle Godinho Araújo; Carvalho, Natália; Siqueira, Ana Paula Silva; Schmidt, Flávio Luís (Multi-Science Journal, 2017)
Não há.